PENERAPAN MODEL TEAMS GAMES TOURNAMENT PADA MATERI EKOSISTEM UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI LAMEU - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
The purpose of this study was to determine the application of the Teams Games Tournament model on theory of ecosystem to improve the learning outcomes of fifth grade students at SD Negeri Lameu. The type of research used is Classroom Action Research (CAR). The subjects of this study were all fifth grade students of SD Negeri Lameu which consisted of 23 students, consisting of 7 female students and 16 male students. The data collection uses instruments, observations, tests and field notes. The results of data analysis showed that in the first cycle the average value obtained by students was 68.26. Meanwhile, KK reached 47.83%. In the second cycle, the students' average score was 77.82, while the KK reached 73.91%. In the third cycle, the students' average score was 83.04 and the KK was 100%.